Ekonomi Perempuan Pesisir Gampong Ujong Blang - Syahputra, Angga; Taufiq, Taufiq (Pusat Studi Gender dan Anak - PSGA (Center for Gender and Child Studies) Institut Agama Islam Negeri Lhokseumawe, Aceh, 2021)
Since Indonesia's independence was proclaimed, women have become the foundation for the development of this nation. Heroes who defended Indonesia during colonialism and imperialism were not only born from men. The role of women as defenders of the homeland cannot be denied. In fishermen's households to increase family income, women usually carry out other activities that can bring in additional income. The same is true for women in Ujong Blang Village, Lhokseumawe. The women who are part of the fishing families try to help the family economy but have not gotten maximum results. For this reason, the service team from FEBI - IAIN Lhokseumawe is here to provide assistance in an effort to empower the economy of coastal women in Ujong Blang Village, Lhokseumawe. In this effort, the team provides training on the use of oysters which can be processed into crackers. Oysters are one of the excess commodities produced by fishermen in Ujong Blang. So far, many oysters have not been sold and have not been used properly. In addition, the team also socialized and demonstrated investment through sharia shares. This investment is expected to be a long-term savings for village women, where part of the processed oyster products can be invested in preparation for the future of the fishing families